Biochemical and Microbiological Changes in Freshwater Catfish (Mystus nemurus V.) During Storage at Different Temperatures - Widjaja, Willy Pranata (2010)
Mystus nemurus is a species of Malaysian freshwater catfish. The freshness of fish is important for quality measurement. Changes in the biochemical components of M. nemurus during storage were analyzed based on lipid changes, formation of amines (volatile and biogenic), pH, and K-Value. Analyses were carried out such as peroxidation by iodometric titration, thiobarbituric acid by spectrophotometry, anisidine value by colorimetry, polyene index by gas chromatography, free fatty acid by acidoalcalimetry titration, K-Value by high performance liquid chromatography (HPLC), volatile base nitrogen by distillation, pH by pH meter, free amino acids by HPLC, and production of biogenic amines by HPLC. The samples were stored at ambient temperature (28±2 oC) for 24 hours, chilled temperature (10±2 oC) for 10 days, and iced temperature (2±1 oC) for 20 days. Lipid oxidation and lipid hydrolysis were significantly increased (p<0.05) by increasing in storage time and temperature with the highest value was 28±2 oC during 24 h. However, polyene index was decrease. The levels of peroxide,thiobarbituric acid, p-anisidine, polyene index and free fatty acid were 2.69 meq active oxygen kg-1 lipids, 17.99 mg malonaldehyde g-1 lipids, 1.28 absorbance g-1, 3.67, and 7.40%, respectively. The K-value of all samples which represent nucleotide degradation reached the spoilage limit of 60% at the end of the storage periods, except for iced treated samples. The total volatile base (TVB) level showed slight differences throughout the storage period. TVB level increased from 17.16 to 45.76 mg N100g-1 at ambient temperature for 24 hours. pH value increased from 6.85 to 7.18 for 24 hours at ambient storage, 6.85 to 7.00 for 10 days at chilled storage and 6.85 to 7.03 for 20 days at iced storage. In this study, 12 hours at ambient, 8 days at chilled, and 16 days at iced temperature showed an unacceptable quality of M. nemurus. The amino acids of histidine, arginine, and lysine decreased along storage time. However, the biogenic amines namely histamine, putrescine, and cadaverine significantly increased (p<0.05) in accordance with the decreased of free amino acids during storage. The kinetic study showed that cadaverine has the highest value of constant rate (k) at 5.380 with activation energy Ea of 3539.9 kcal mol-1 at ambient storage. Therefore, in biochemical study cadaverine could be considered as spoilage indicator for M. nemurus for all storage temperatures. Studies on the bacteriological changes of pond water were also carried out to evaluate the relationship between water quality and microbiological changes during storage of M. nemurus. The analyses involved were total mesophilic and psychrophilic aerobic count, lipase-producing bacterial count by plate count agar, proteolytic bacterial count by skim milk agar, histamine-producing bacterial count by modified Niven’s agar, putrescine producing bacterial count by arginine decarboxylase agar, cadaverine-producing bacteria count by lysine decarboxylase agar and Pseudomonas count by cetrimide fusidin cepaloridine agar, and lipolytic activity by Rodhamine-β olive oil agar. For 20 days of iced storage, the total mesophilic aerobic count increased from log 5.12 CFU g-1 to log 7.30 CFU g-1. Psychrophilic bacterial count also increased for both 10 days of chilled storage and 20 days of iced storage. However, this result was slightly lower in one log cycle than mesophilic count. The lipase-producing bacterial count showed increase for all storage temperatures. Total mesophilic proteolytic count increased significantly (p<0.05) and attained a maximum level of 6.61 CFU g-1 at the end of 20 days of iced storage. The same trend was observed for total psychrophilic proteolytic count. The count for cadaverine-producing bacteria was the highest as compared to the other amine-forming bacteria. The count of Pseudomonas spp. that contributed to the highest production of cadaverine reached the value of log 7.20 CFU g-1 for 20 days in iced storage could be a dominance indicator for the decomposition of M. nemurus during storage.